PROVIDING CUSTOMER SATISFACTION THROUGH EXCELLENT SERVICE OF BUTLERS IN SAMAJA VILLA KUNTI SEMINYAK - Putu Gede Winatha Dharma; Ketut Redjasa; Made Sudiarta; Gede Ginaya; Ketut Budarma (Politeknik Negeri Bali, 2018)
This research will explain about how the implementation and execution of a butler work in a villa by providing maximum service and commonly referred to as excellent service. In this study requires a long time and many factors that must support this research include: the existence of some opinions and theories of experts related to research, then the method used to conduct research. To examine how the application of excellent service by butler to improve customer satisfaction at Samaja Villa Kunti Seminyak requires qualitative descriptive analysis technique. This research method does not require calculation in the form of numbers, just enough to require reliable respondents to provide information and related data clearly with research methods by observation, interview, decommissioning, and literature study or by finding related sources in the book. Interview data in this research is the main data source which become the material of data analysis to answer the problem in this research. Data analysis began by conducting in-depth interviews with informants. After conducting the interview, the researcher transcribed the interview result by replaying the interview record and then writing the words according to what was recorded. After the researchers write the results of the interview into the transcript, the next researcher made the data reduction by means of abstraction, that is taking the data in accordance with the research context and ignoring the data that is not needed. Data analysis in qualitative research is done when data collection takes place in field, and after completion of data collection in certain period. At the time of the interview, the researcher has done an analysis of the answered interviewee. If the answer interviewee after the analysis feels unsatisfactory, then the researcher will continue the question again until a certain stage, obtained credible data. Then proceed with steps such as data reduction, data presentation, and conclusion drawing or verification.